The Role of Spiritual Guidance for the Patient in Reinterpreting Pain At Al-Irsyad Hospital in Surabaya - Nurhidayati, Nurhidayati; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2018)
Patient Companions (spiritual guidance for patients) at Al-Irsyad Hospital in Surabaya has been around since 2013. Al-Irsyad Hospital is an Islamic hospital that involves 'Friends of Patients' who can provide spiritual needs even when needed to strengthen the patient's mind in the process of healing. The construction process carried out by Friends of Patients is not only for patients but also for all components of the hospital, especially for employees as an Islamic hospital culture. The theoretical framework of this study is the social construction of Peter L Berger and Thomas Luckman. This type of research is qualitative research and how to determine the informants in this study using purposive techniques. Retrieval of data using observation, interviews, and documentation. While the data validity test in this study uses data triangulation, the findings of this study indicate that there is a change in perspective regarding pain, among others, illness is a trial and test from God. Illness is a form of forgiveness of sins and errors of God. The disease also elevates human degrees. Therefore, patients can reinterpret the meaning of the pain they are suffering from and realize that they are God's creatures. Keywords: spiritual needs, Islamic hospitals, a reinterpretation of illness, illness, patients. Referensi: Arifin, Isep Zainal. 2012. Bimbingan dan Konseling Islam untuk Pasien Rawat Inap di Rumah Sakit. Jurnal Ilmu Dakwah, 6 (19) Praktikya, Ahmad Watik dan Abdul Salam M. Sofro, 1985, Islam, Etika, dan Kesehatan. Jakarta: CV Rajawali Sunaryo. 2014. Sosiologi untuk Keperawatan. Jakarta: Bumi Medika. Parsons, T (dalam Sunaryo). 2014. Sosiologi untuk Keperawatan. Jakarta: Bumi Medika. Luckman, dan Berger. 1990. Tafsir Sosial atas Kenyataan. Jakarta: LP3S. Sudarma. 2012. Sosiologi untuk Kesehatan. Jakarta: Salemba Medika. Faqih, Ainurrohim. 2000. Bimbingan Konseling dalam Islam. Yogyakarta: UII Press.